How we think they see us? Valence and difficulty of retrieval as moderators of the effect of meta-stereotype activation on intergroup orientations. - Vázquez, Alexandra; Yzerbyt, Vincent; Dovidio, John F; Gómez, Ángel (International journal of psychology : Journal international de psychologie, 2016)
Previous research indicates that meta-stereotypes are predominantly negative. However, the valence of the meta-stereotypes may not be the only factor accounting for the detrimental effects associated with their activation. In addition to valence, we propose that the subjective difficulty of retrieving the meta-stereotype might critically determine whether its activation deteriorates intergroup orientations. An experimental study showed that the effect of the meta-stereotype activation on the desire to interact with outgroup members was moderated by the interaction between the valence of the meta-stereotype and its difficulty of retrieval. In particular, the activation of a positive meta-stereotype deteriorated intergroup orientations when the difficulty of retrieval was high as compared with a condition in which the difficulty of retrieval was low. In sharp contrast, the activation of a negative meta-stereotype worsened intergroup orientations when the difficulty of retrieval was low as compared with a condition in which the difficulty of retrieval was high.